Verdade, corpo de delito e punição Na Colônia Penal, de Franz Kafka: encontros e desencontros entre as tessituras narrativas dos discursos literário e jurídico - Lima, Lidiany Caixeta de (2021)
Throughout this research, I tried to demonstrate the possible links between literary and legal studies mediated by the analysis of the narrative In the Penal Colony, by Franz Kafka. For this, I highlighted some important spects for an approach to the tale, with regard to my perception of a criticism of the legal discourse and the punitive system, present in the tale. Considering this direction, I discussed how the compositional elements of the narrative are presented, considering the literary discourse and legal discourse, relating them to the truth, the criminal body and, also, to the penalty, present in the narrative under study. As the studies progressed, I understood the intricate relationship between literary and legal narrative, in view of the reader's involvement by the impact of the defendant's execution scene by the device, in addition to the affective and emotional sensitivity that the plot situations allow to feel. Through the eyes of the explorer, the reader of In the Penal Colony has the possibility of getting to know the Penal Colony and the peculiar system of torture, recognizing the officer's fanaticism and idolatry for the apparatus, the prisoner 's resignation, the guard 's blind obedience. The narrative's aesthetic experience enables the reader to be, like the explorer (traveller), an observer of the apparatus and the personalities that inhabit the place, being led, at the end of the reading, to take a position on the application of punitive norms by the odd apparatus, since the view of the procedure as torture belongs to the foreigner and, to a large extent, to the reader.